(untitled) (Nonconventional Technologies Review, 2021)
Rectilinear kerfs in workpieces made of hard electroconductive materials can be made by wire erosion electrical discharge machining. However, since machine tools intended for such machining are rarer and more expensive, the problem of using devices for wire electrical discharge machining, but adaptable to ram electrical discharge machines, has been formulated. The identification of the functional requirements for such a device in accordance with the principles of axiomatic design led to the defining of a device solution flexible enough to be able to be adapted to different machining conditions. In the constructive solution of the device were incorporated subsystems for pulling and guiding the wire electrode, for changing the angular position of the wire electrode in the machining. The realization and preliminary experimentation of the device led to the formulation of some suggestions for improving the constructive solution of the device.